Pengaruh Elemen Visual pada Konten Feeds Instagram @P3SMANDIRI dalam meningkatkan Brand awareness - Muhamad Ilham Awaludin; Sakundria Satya Murti Wardhana (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
This study aims to analyze the impact of visual elements on the Instagram feed content of the @P3SMANDIRI account on increasing brand awareness using a quantitative approach. In an increasingly competitive digital marketing ecosystem, visual elements such as color, typography, layout, illustration, and graphic design are often considered important components that can shape consumer perceptions of a brand. However, there is still limited research that specifically examines how these visual elements contribute to increasing brand awareness, especially on social media platforms such as Instagram. This study was conducted by collecting data through a survey using a Likert scale as a measurement instrument. This survey was distributed to 100 respondents who were Instagram users and also followers of the @P3SMANDIRI Instagram account. The data obtained were analyzed quantitatively using SPSS statistical software to map the relationship between visual elements and brand awareness. The main focus of this survey was to identify and evaluate which visual elements were the most influential in attracting user attention while encouraging increased brand awareness. The results of this study provide in-depth insights into the role of visual strategies in increasing brand awareness, showing that effective visual elements can significantly influence audience perception and engagement with a brand, and provide practical guidance for marketers in designing effective visual content on social media. The conclusions of this study highlight the importance of implementing a planned visual strategy in digital marketing activities, especially on social media such as Instagram. This study not only provides practical insights for marketers in designing effective visual content but also enriches the academic literature on the role of visual elements in building brand awareness in the social media ecosystem.